2000
DOI: 10.1097/00004728-200009000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Unenhanced Helical CT Using Increased Pitch for Suspected Renal Colic: An Effective Technique for Radiation Dose Reduction?

Abstract: Increasing the pitch on unenhanced helical CT for suspected renal colic to 2.5 or 3.0 appears to be an effective method of reducing radiation dose. Although accuracy of the technique did not significantly change using a pitch of 3.0 in one group of patients, compared with a pitch of 2.5 in another group of patients, image quality did decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The researchers primarily evaluated the possibility of reducing the dose by increasing the pitch, 8 lowering the tube current, 9-11 using automatic tube current modulation, 12 reducing the tube voltage 13,14 and using iterative reconstruction algorithms. [13][14][15][16][17][18][19] Another simple and effective way to reduce the dose is to limit acquisition coverage from the top of the kidneys to the lower edge of the bladder.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The researchers primarily evaluated the possibility of reducing the dose by increasing the pitch, 8 lowering the tube current, 9-11 using automatic tube current modulation, 12 reducing the tube voltage 13,14 and using iterative reconstruction algorithms. [13][14][15][16][17][18][19] Another simple and effective way to reduce the dose is to limit acquisition coverage from the top of the kidneys to the lower edge of the bladder.…”
Section: Introductionmentioning
confidence: 99%
“…Several dose-reduction techniques, such as tube current modulation [5], reduced tube voltage [6], use of a higher pitch [7] and noise reduction filters [8], have been successfully implemented and have been shown to reduce radiation exposure. However, further reductions in radiation dose are hindered by increased image noise and degraded image quality, mainly as a result of limitations of the standard filtered back projection (FBP) reconstruction algorithm currently used on most CT systems.…”
Section: Introductionmentioning
confidence: 99%
“…As for pitch, an increase in pitch decreases duration of examination and also decreases radiation exposure to the body. Although increase of pitch causes helical artifacts and decreased spatial resolution, some investigators have reported using a pitch of 2 or above with satisfactory results in cases of suspected renal colic (20,21).…”
Section: Radiation Dose Optimization and Dose Reduction: Alara (As Lomentioning
confidence: 99%